The role of bioactive lipids in attenuating the neuroinflammatory cascade in traumatic brain injury - Poblete, Roy A. (Ann Clin Transl Neurol, 2020)
Traumatic brain injury (TBI) is a major cause of morbidity, mortality, and economic burden. Despite this, there are no proven medical therapies in the pharmacologic management of TBI. A better understanding of disease pathophysiology might lead to novel approaches. In one area of increasing interest, bioactive lipids known to attenuate inflammation might serve as an important biomarker and mediator of disease after TBI. In this review, we describe the pathophysiology of inflammation following TBI, the actions of endogenous bioactive lipids in attenuating neuroinflammation, and their possible therapeutic role in the management of TBI. In particular, specialized pro‐resolving lipid mediators (SPMs) of inflammation represent endogenous compounds that might serve as important biomarkers of disease and potential therapeutic targets. We aim to discuss the current literature from animal models of TBI and limited human experiences that suggest that bioactive lipids and SPMs are mechanistically important to TBI recovery, and by doing so, aim to highlight the need for further clinical and translational research. Early investigations of dietary and parenteral supplementation of pro‐resolving bioactive lipids have been promising. Given the high morbidity and mortality that occurs with TBI, novel approaches are needed.